The Transcriptional Control of Iron Homeostasis in Plants: A Tale of bHLH Transcription Factors? - Gao, Fei; Robe, Kevin; Gaymard, Frederic; Izquierdo, Esther; Dubos, Christian (Frontiers in Plant Science, 2019)
Iron is one of the most important micronutrients in plants as it is involved in many cellular functions (e.g. photosynthesis, respiration). Any defect in iron availability will affect plant growth and development as well as crop yield and plant product quality. Thus, iron homeostasis must be tightly controlled in order to ensure optimal absorption of this mineral element. Understanding mechanisms governing iron homeostasis in plants has been the focus of several studies during the past 10 years. These studies have greatly improved our understanding of the mechanisms involved, revealing a sophisticated iron-dependent transcriptional regulatory network. Strikingly, these studies have also highlighted that this regulatory web relies on the activity of numerous transcriptional regulators that belong to the same group of transcription factors, the bHLH (basic helix-loop-helix) family. This is best exemplified in Arabidopsis where, to date, 16 bHLH transcription factors have been characterized as involved in this process and acting in a complex regulatory cascade. Interestingly, among these bHLH transcription factors some form specific clades, indicating that peculiar function dedicated to the maintenance of iron homeostasis, have emerged during the course of the evolution of the green lineage. Within this mini review, we present new insights on the control of iron homeostasis and the involvement of bHLH transcription factors in this metabolic process.